The Impact of Public Sector Social Expenditures and Capital Formation on Economic Growth in Türkiye: A Fourier-Augmented ARDL Approach - Hakan Ateş; Fatih Akın; Ali Şen (Hak İş Uluslararası Emek ve Toplum Dergisi, 2026)
Understanding the determinants of economic growth is a fundamental issue in macroeconomic policy discussions. This study examines the effects of public sector social expenditures and capital formation on economic growth in the Turkish economy. Annual data from 1995-2024 were used, and the Fourier-Augmented ARDL approach was employed to account for structural changes occurring during the period under review. The findings indicate that capital formation has a positive and statistically significant effect on economic growth, while the effect of public sector social expenditures is negative and statistically significant. Short-run results show that the contemporaneous and one-period lagged effects of capital formation are positive, while the contemporaneous effect of public sector social expenditures is negative. These findings highlight the importance of policies supporting capital formation for growth in Türkiye and suggest a need to re-evaluate the composition and efficiency of social expenditures.